2018
DOI: 10.1002/bdr2.1356
|View full text |Cite
|
Sign up to set email alerts
|

Folate transporter expression in placenta from pregnancies complicated with birth defects

Abstract: The expression of PCFT in placentas from BD-complicated pregnancies is increased, possibly as an adaptive response to increase the folate flux at the maternal-fetal interface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
(25 reference statements)
0
3
3
Order By: Relevance
“…Contrary to our hypothesis, we found no differences in semi‐quantitative assessments of placental folate transporter protein localization or expression (for FRα, PCFT, and RFC) across study groups, and no associations between placental folate transporter expression and birthweight. Our findings are inconsistent with previous studies from India and Mexico, which have reported upregulated FRα and RFC expression in placentae from fetuses with NTDs, 20 and upregulated PCFT expression in placentae from fetuses with congenital anomalies (including, but not limited to, NTDs) 43 . India does not have mandatory folic acid fortification 44 and folic acid fortification in Mexico is not well enforced, 45 suggesting that suboptimal maternal folate status may have contributed to the changes observed in placental folate transport in those studies.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to our hypothesis, we found no differences in semi‐quantitative assessments of placental folate transporter protein localization or expression (for FRα, PCFT, and RFC) across study groups, and no associations between placental folate transporter expression and birthweight. Our findings are inconsistent with previous studies from India and Mexico, which have reported upregulated FRα and RFC expression in placentae from fetuses with NTDs, 20 and upregulated PCFT expression in placentae from fetuses with congenital anomalies (including, but not limited to, NTDs) 43 . India does not have mandatory folic acid fortification 44 and folic acid fortification in Mexico is not well enforced, 45 suggesting that suboptimal maternal folate status may have contributed to the changes observed in placental folate transport in those studies.…”
Section: Discussioncontrasting
confidence: 99%
“…Because folate deficiency is a well-established risk factor for NTDs [1][2][3] and may contribute to poor fetal growth, 5 20 and upregulated PCFT expression in placentae from fetuses with congenital anomalies (including, but not limited to, NTDs). 43 India does not have mandatory folic acid fortification 44 and folic acid fortification in Mexico is not well enforced, 45 suggesting that suboptimal maternal folate status may have contributed to the changes observed in placental folate transport in those studies.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to our hypothesis, we found no differences in semi-quantitative assessments of placental folate transporter protein localisation or expression (for FRα, PCFT, and RFC) across study groups, and no associations between placental folate transporter expression and birthweight. Our findings are inconsistent with previous studies from India and Mexico, which have reported upregulated FRα and RFC expression in placentae from fetuses with NTDs 21 , and upregulated PCFT expression in placentae from fetuses with congenital anomalies (including, but not limited to, NTDs) 45 . India does not have mandatory folic acid fortification 46 and folic acid fortification in Mexico is not well enforced 47 , suggesting that suboptimal maternal folate status may have contributed to the changes observed in placental folate transport in these studies.…”
Section: Discussioncontrasting
confidence: 99%
“…Contrary to our hypothesis, we found no differences in semi-quantitative assessments of placental folate transporter protein localisation or expression (for FRα, PCFT, and RFC) across study groups, and no associations between placental folate transporter expression and birthweight. Our findings are inconsistent with previous studies from India and Mexico, which have reported upregulated FRα and RFC expression in placentae from fetuses with NTDs 315 , and upregulated PCFT expression in placentae from fetuses with congenital anomalies (including, but not limited to, NTDs) 330 . While data on maternal folate status were not available in either study, India does not have mandatory folic acid fortification 331 and folic acid fortification in Mexico is not well enforced 332 , suggesting that suboptimal maternal folate status may have contributed to the changes observed in placental folate transport in these studies.…”
Section: Discussioncontrasting
confidence: 99%